Pengaruh Kompensasi Finansial, Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Karyawan PT. Reads Media Corp - Nursahdi Saleh (Journal of Career Development, 2023)
This study aims to determine and analyze: the influence of Financial Compensation, Leadership, Organizational Culture partially and simultaneously on the performance of employees at PT. Reads Media Corp., as well as the most dominant variable affecting the performance of employees at PT. Reads Media Corp...This research approach uses survey research. Research conducted at PT. Reads Media Corp.. When the research was conducted from September 2022 to November 2022. The research population was all employees of PT. Reads Media Corp. which totaled 48 people. The selection of the sample in this study was carried out using the saturated sampling method (census), namely by determining the entire population as a total sample of 48 employees. Data analysis using multiple regression analysis (multiple regression analysis). The results showed that: 1) There is a positive and significant influence of Financial Compensation, Leadership, Organizational Culture separately (partially) on the performance of employees of PT. Reads Media Corp., with tcount = 6.022., 8.211 and 6.118 table = 2.00., 2) There is a positive and significant effect of Financial Compensation, Leadership, Organizational Culture simultaneously (simultaneously) on the performance of employees of PT. Reads Media Corp., where Fitung = 3.012 Fable = 2.65., and 3) The most dominant financial compensation variable on the performance of employees of PT. Reads Media Corp. seen from the value of the greatest determination that is 0.594.